Ultra-Orthodox Parents' Perceptions of Arts Therapies for Their Children - Lali Keidar; Sharon Snir; Dafna Regev; Eliav Keidar (MDPI AG, 2022)
Studies have underscored the complexity of psychotherapy for Ultra-Orthodox Jews, and cross-cultural therapy in particular, which evokes fear of disruption of basic values. Parents' sense of responsibility for their child's religious education exacerbates these problems in child therapy. However, there is scant research on child therapy for the Ultra-Orthodox, especially in the field of arts therapies. The present study examined the perceptions of 17 Ultra-Orthodox parents whose children were receiving arts therapies (including art therapy, dance/movement therapy, music therapy, psychodrama and bibliotherapy). Semi-structured interviews were conducted with the parents and analyzed based on the principles of Consensual Qualitative Research. The study covered five domains: (1) The parents' experiences in therapy; (2) The parents' perceptions of the child's experiences in therapy; (3) Implications of environmental-social factors on the parents' perceptions and experiences of therapy; (4) Effects of intercultural aspects on therapy; (5) Perceptions of the use of the arts in therapy. The findings show that the experiences of ultra-Orthodox parents in the arts therapies of their children is complex due to the influence of the socio-cultural context, which involves dealing with stigma and tensions in their relationship with the education system. This context also shapes their perceptions of therapy, which can be characterized as purpose-oriented. The findings also highlight the parents' challenges in coping with the intercultural therapeutic relationship, and emphasizes the parents' preference for a therapist from a similar religious/cultural background and for cultural supervision of therapy. However, the results also suggest that there are benefits inherent to intercultural therapy in general and arts therapies in particular, including a sense of security, openness and acceptance of the parents and children.